Análise das causas socioeconômicas da pobreza rural no Ceará - Mendonça, Kamila Vieira de (2009)
The poverty aims to analyse in the rural areas in the State of the Ceará in which it refers to his causes socioeconomics, like education, age, color, type, principal activity of occupation and government transfers. Besides, there aim to analyse the characteristics of the rural residences made a list to the acess the public goods. There are studied the causes of the rural pverty of Ceará with the objective to check possible alterations in the level of the poverty in the previous and subsequent period of the Real Plan. From the microdata of the PNAD, obtained near the IBGE, there are determined the variables that present association with the rural poverty, through the model of regression logit and to analyse the determinants of the individuals, the marginal contributions are calculated. Besides, the public goods are calculated the descriptive statistics of the variable made a list to the causes of the poverty and to the acess. It is ended that the variables sex, level of schooling, receiving of retirement, boarding house and principal activity of work have significant relation with the poverty o the region, being the principals to education and the government transfers. Besides, it increased the acess to the public goods, this fact that provided better quality of life for the rural population of Ceará.